Buy and sale bonding agreements as a mean of fraud legal relation debt receivables - James Pala Joewono; Isnaeni; Endang Prasetyawati; Krisnadi Nasution (Technium Social Sciences Journal, 2022)
This research is a normative legal research. Perjanjian Pengikatan Jual Beli (PPJB) it can be said to be an agreement that arises or is born to due open nature Book III BW so that the implementation of previously unknown agreements such as PJBB is possible based on the principle of contact freedom. Accounts payable begins with an agreement called a debt agreement, but in practice the general public turns out to make a lot of quasi or fake agreements by making a deed of money debt agreement with land certificates or house certificates as collateral then packaged as PPJB. PPJB which is used to disguise debt is actually an agreement that is legally deviant. Legally deviant contracts are made by parties who are in a depressed position and there is no element of agreement of the will and it is an abuse of circumstances.